MORPHOLOGICAL AND CHEMICAL VARIABILITY OF LEBANESE CAROB VARIETIES - Amira Haddarah; Ali Ismail; Ali Bassal; Tayssir Hamieh; Irina Ioannou; Mohamed Ghoul (European Scientific Journal, ESJ, 2013)
Morphological variation (pod length, width, thickness, seed number, volume, weight and specific gravity measurements) and chemical composition (protein, sugar, fiber, ash and total phenol content) of nine carob varieties from different regions of Lebanon were investigated. The obtained results showed that these two criteria exhibit significant differences (p<0.05) allowing thus to establish correlations between morphological aspects and location, mainly latitude. Moreover, the principal component analysis (PCA) of the data allowed separating these varieties in two grouped and two ungrouped populations.